Evaluation of Intracranial Hypertension in Patients With Hypertensive Intracerebral Hemorrhage Using Texture Analysis - Shan, Yingchi; Li, Yihua; Wu, Xiang; Liu, Jiaqi; Zhang, Guoqing; Xue, Yajun; Gao, Guoyi (Frontiers in Neurology, 2022)
Purpose: Texture analysis based on clinical images had been widely used in neurological diseases. This study aimed to achieve depth information of computed tomography (CT) images by texture analysis and to establish a model for noninvasive evaluation of intracranial pressure (ICP) in patients with hypertensive intracerebral hemorrhage (HICH). Methods: Forty-seven patients with HICH were selected. Related CT images and ICP value were collected. The morphological features of hematoma volume, midline shift and ventriculocranial ratio were measured. Forty textural features were extracted from regions of interest. Four models were established to predict intracranial hypertension with morphological features, textural features of anterior horn, textural features of temporal lobe and textural features of posterior horn. Results: Model of posterior horn had the highest ability to predict intracranial hypertension, followed by model of anterior horn and model of temporal lobe, and model of morphological features displayed the worst performance. Conclusion: Texture analysis can realize interpretation of CT images in depth, which has great potential in noninvasive evaluation of intracranial hypertension.